PROGRESSIVE GOVERNANCE SYSTEM AGAINST THE SHIFTING DYNAMICS OF CHILDREN'S BEHAVIOR, CHILDREN'S PSYCHOLOGY, AND CHILDREN'S LANGUAGE PHASE - Nafisah; Imam Mahdi; Moch. Iqbal (Esteem Journal of English Education Study Programme, 2024)
The Teenage Curriculum should be implemented in schools as a means of helping students develop their moral and spiritual awareness as well as their ability to fulfill their social and religious obligations. This is the topic of this study. This curriculum incorporates student-centered learning and places a strong emphasis on Christian principles and character education. In order to help pupils gain a comprehensive knowledge, the teacher facilitates discussions that help them grasp moral and religious ideas. The Teenage Curriculum's implementation also takes Islamic beliefs and morals into consideration, which can help pupils navigate the problems of life.